It's only teeth - are there limits to genetic testing? - Aldred, M; Crawford, P; Savarirayan, R; Savulescu, J (2003)
Dental genetic disorders can cause severe social and psychological effects in affected individuals. The cost of treatment can be considerable, not only in financial terms but also in time spent during treatment. In theory it is, or will soon be, possible to use advances in molecular genetics for pre-natal testing, for selection of embryos using in vitro fertilization techniques, and for gene therapy. The questions we pose are whether these approaches are appropriate. We hope that this review will stimulate debate on these issues.